A sociedade civil brasileira e a cooperaç\~ao sul-sul para o desenvolvimento: O caso do Viva Rio no Haiti - Guilherme de Oliveira Schmitz (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The objective of this study is to analyze some of the factors that influence the process of internationalization of Brazilian civil society as a partner for economic and social development in other countries, from the experience of the Non-Governmental Development Organization (NGDO) Viva Brazil Rio in Haiti. Although considered a successful experience, Viva Rio faced a number of obstacles in expanding its international reach, and was not yet followed by a similar movement from other Brazilian NGO's, despite support from the Brazilian government, the United Nations (UN) and other institutions from developed countries. By analyzing the ways by which the national government, international organizations, transnational corporations and NGDOs interact with Northern NGDOs of the global South, it becomes clear that the international capabilities of Brazilian NGDO's are still constrained due to the incipient internationalization of both Brazilian society and government.
Keywords: F35; L31; K34; 330; foreign policy; South-South Cooperation for Development; non-governmental organizations; global civil society